Sistem Keamanan Siber dan Kedaulatan Data di Indonesia dalam Perspektif Ekonomi Politik (Studi Kasus Perlindungan Data Pribadi) [Cyber Security System and Data Sovereignty in Indonesia in Political Economic Perspective] - Aji, Muhammad Prakoso (Jurnal Politica, 2022)
Cyber security system and data sovereignty is the foundation in realizing the protection of personal data. Technological developments place data into a very valuable commodity. In the aspect of political economy, data sovereignty of a country is faced with the position of the state with the private sector in a global context. The main role of the state is to produce cyber data protection and cyber security regulations. Guaranteed protection of personal data is a citizen’s right that requires the capacity and capability of citizens. A state centered approach is often used in cyber security development. However, without a people centered approach, it will be difficult to realize protection and protection for citizens regarding their personal data which is very valuable. For this reason, this research will look at how the capacity and capability development of citizens is needed in the development of cyber security and data sovereignty related to the protection of personal data in Indonesia. The author chose qualitative research methods to facilitate the collection of data obtained through books, journal articles, online media, and other sources. The results of the study indicate that the dominance of the state-centered approach in cybersecurity development has not realized national data sovereignty, as well as the protection of the protection of the personal data of each citizen. Building the capacity and capability of citizens is very necessary to protect their personal data in cyberspace.AbstrakSistem keamanan siber dan kedaulatan data merupakan pondasi dalam mewujudkan perlindungan data pribadi. Perkembangan teknologi menempatkan data menjadi sesuatu komoditi yang sangat bernilai. Dalam aspek ekonomi politik, kedaulatan data suatu negara dihadapkan pada posisi negara dengan sektor swasta dalam konteks global. Peran negara utamanya adalah untuk menghasilkan regulasi perlindungan data siber dan keamanan siber. Jaminan perlindungan data pribadi merupakan hak warga negara yang membutuhkan kapasitas dan kapabilitas warga negara. Pendekatan berbasis state centered seringkali digunakan dalam pembangunan keamanan siber. Akan tetapi, tanpa pendekatan yang bersifat people centered akan sulit untuk mewujudkan perlindungan dan proteksi bagi warga negara terkait data pribadinya yang sangat bernilai. Untuk itu, penelitian ini akan melihat bagaimana pembangunan kapasitas dan kapabilitas warga negara diperlukan dalam pembangunan keamanan siber dan kedaulatan data terkait perlindungan data pribadi di Indonesia. Penulis memilih metode penelitian kualitatif untuk mempermudah pengumpulan data yang didapatkan lewat buku, artikel jurnal, media daring, dan sumber-sumber lainnya. Hasil penelitian menunjukkan bahwa dominasi pendekatan negara yang bersifat state centered dalam pembangunan keamanan siber belum mewujudkan kedaulatan data secara nasional, juga proteksi perlindungan data pribadi masing-masing warga negara. Pembangunan kapasitas dan kapabilitas warga negara sangat diperlukan untuk melindungi data-data pribadinya di ruang siber.